Animal husbandry and hunting in the central and western Balkans through time - Marković, Nemanja,; Bulatović, Jelena, (Archaeopress Archaeology, 2020)
This volume presents the results of new research on animal herding and hunting in the central and western Balkans during the prehistoric and historic periods. The investigations cover a wide range of topics related to animal exploitation strategies, ranging from broad syntheses to specific case studies.